Guide to fashion career planning job search, resumes, and strategies for success - Paulins, V. Ann; Hillery, Julie L. (New York Fairchild Books, 2016)
"Helps both students and individuals interested in entering the fashion industry prepare fur successful careers-- from self-assessment and goal setting to landing the first job. The book presents a seamless and comprehensive approach to everything needed for professional and career development." --back cover.
Introduction to the industry -- Preparing to work in the industry -- Identifying and branding your professional profile -- Developing your professional portfolio -- The job search and networking -- resumes and cover letters -- Interviewing -- Work experiences and internships -- Professional ethics -- Transitioning form college to career.
Includes bibliographical references and index.
Keywords: Fashion design -- Vocational guidance